Application of Cryptography and Steganography Techniques to Improving the Security of Text Messages with RC4 Algorithm and MSB Method - Ihsan, Ihsan Muchlis; Achmad Fauzi; Husnul Khair (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
This study discusses the application of cryptography and steganography techniques to improve the security of text messages using the Rivest Code 4 (RC4) algorithm and the Most Significant Bit (MSB) method. In the ever-growing digital era, data security is a top priority due to the increasing threat of cybercrime that can harm many parties. RC4 is a cryptography algorithm known for its encryption and decryption speed, while the MSB method is an effective steganography technique for hiding information in digital images. This study aims to develop an application that is able to encrypt text messages with the RC4 algorithm and hide them in digital images using the MSB method. With this combination, data is not only encrypted but also hidden, thus providing two layers of security to protect information from unauthorized access. The results of the study show that the combination of RC4 cryptography and MSB steganography techniques successfully improves data security well. The developed application is able to protect sensitive information from the risk of data theft and cyber attacks. In addition, this technique is also easy to implement and can be applied in various sectors, such as banking, health, and business communications, to protect sensitive data from unauthorized access. Keywords: Cryptography, Steganography, Most Significant Bit (MSB)